2005
DOI: 10.1073/pnas.0501203102
|View full text |Cite|
|
Sign up to set email alerts
|

Cyclin-dependent kinase 6 associates with the androgen receptor and enhances its transcriptional activity in prostate cancer cells

Abstract: Cyclin-dependent kinase 6 (CDK6) binds to and is activated by cyclin D1 and thereby enhances the transition of cells through the G1 phase of the cell cycle. The present study indicates that, in human prostate cancer cells, CDK6 can also bind to the androgen receptor (AR) and stimulate its transcriptional activity in the presence of dihydrotestosterone. This effect of CDK6 does not require its kinase activity and is inhibited by cyclin D1 and p16INK4a. The T877A mutant of the AR frequently found in advanced cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 23 publications
1
74
0
Order By: Relevance
“…It should also be noted that, although Cdk2 and Cdk5 did not enhance AR Ser-81 phosphorylation or expression, other Cdks may contribute to the effects of Cdk antagonists in PCa cells, including possible roles for Cdk7 and Cdk9 in regulating AR message levels. Significantly, previous studies have identified AR interactions with Cdk6 and Cdk7, whereas Cdk2 has been reported to interact with the progesterone receptor (46)(47)(48)(49). We have used Cdk1 siRNA and short hairpin RNA (shRNA) in efforts to further assess the role of Cdk1, but Cdk1 is required for mitosis, and it has not yet been possible to generate Cdk1-depleted PCa cells.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that, although Cdk2 and Cdk5 did not enhance AR Ser-81 phosphorylation or expression, other Cdks may contribute to the effects of Cdk antagonists in PCa cells, including possible roles for Cdk7 and Cdk9 in regulating AR message levels. Significantly, previous studies have identified AR interactions with Cdk6 and Cdk7, whereas Cdk2 has been reported to interact with the progesterone receptor (46)(47)(48)(49). We have used Cdk1 siRNA and short hairpin RNA (shRNA) in efforts to further assess the role of Cdk1, but Cdk1 is required for mitosis, and it has not yet been possible to generate Cdk1-depleted PCa cells.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] In addition, CDK6 negates the ability of cyclin D1 to suppress AR function, and can serve to heighten AR activity independent of it skinase function. 37 In G 2 , CDK1 activity has been shown to promote AR phosphorylation and stabilization, resulting in increased AR activity. 38 Lastly, it was recently shown that AR is degraded in mitosis; although this latter observation was reported to suggest a putative "licensing" function for AR in controlling DNA replication, this concept has yet to be tested.…”
Section: Ar-mediated Cell Cycle Progressionmentioning
confidence: 99%
“…[35][36][37] CDK6 is overexpressed in lymphoma, leukemia, glioma, glioblastoma, medulloblastoma, and cancers of squamous cells, salivary gland, bladder, pancreas and prostate. [38][39][40][41][42][43][44][45][46][47][48][49][50] In human prostate cancer cells, CDK6 has also been shown to bind androgen receptor and stimulate its activity in a kinase activity independent manner. 46 Blockage of CDK6 expression by microRNAs (miRNAs) has been shown to inhibit the proliferation of gliomas, medulloblastoma, prostate, bladder, gastric, hepatocellular, and lung cancer cells, indicating the significant role of CDK6 in the initiation and progression of these cancers.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41][42][43][44][45][46][47][48][49][50] In human prostate cancer cells, CDK6 has also been shown to bind androgen receptor and stimulate its activity in a kinase activity independent manner. 46 Blockage of CDK6 expression by microRNAs (miRNAs) has been shown to inhibit the proliferation of gliomas, medulloblastoma, prostate, bladder, gastric, hepatocellular, and lung cancer cells, indicating the significant role of CDK6 in the initiation and progression of these cancers. [51][52][53][54][55][56][57][58] These observations, coupled with the fact that mice lacking D-type cyclins and/or CDK4/6 are viable, make targeting components of the CDK4/6 cyclin D-INK4-pRb-E2F pathway a highly attractive anti-cancer strategy.…”
Section: Introductionmentioning
confidence: 99%